2010
DOI: 10.1158/1940-6207.prev-10-a52
|View full text |Cite
|
Sign up to set email alerts
|

Abstract A52: Koetjapic acid suppresses angiogenesis causing inhibition in VEGF expression

Abstract: Koetjapic acid is a naturally occurring ichthyotoxic compound which can be isolated from the stem bark of Sandricum keotjape. This is a large tree species that can be found widely in Malaysia and other tropical countries in Southeast Asia. In our studies, we found koetjapic acid to be strongly antiangiogenic causing significant inhibition in endothelial tube formation. The compound inhibited VEGFA expression and caused retardation in cell migration. Keotjapic acid also suppressed the activity of Hif-1a and up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The antiangiogenic properties of KJA can be associated with its targeting of angiogenesis cascades. It exerts its antiangiogenic effects by inhibiting the formation of new blood cells, migration and differentiation of endothelial cells and expression of VEGF factor, which is the main positive angiogenic factor [ 45 , 46 ]. The metastasis is another significant event in carcinogenesis, which consists of multiple steps including cell survival, colony formation, migration and invasion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antiangiogenic properties of KJA can be associated with its targeting of angiogenesis cascades. It exerts its antiangiogenic effects by inhibiting the formation of new blood cells, migration and differentiation of endothelial cells and expression of VEGF factor, which is the main positive angiogenic factor [ 45 , 46 ]. The metastasis is another significant event in carcinogenesis, which consists of multiple steps including cell survival, colony formation, migration and invasion.…”
Section: Introductionmentioning
confidence: 99%
“…Nassar et al have shown that treating KJA on Human Umbilical Vein Endothelial Cells (HUVECs) demonstrates its anti-angiogenic activity. KJA has been shown to have low-cytotoxicity against HUVECs with IC-50 of 40.97 μg/ml, where KJA was found to inhibit the vasculogenesis by alleviating the expression of VEGF, migration of endothelial cells as well as differentiation [ 3 , 4 , 11 , 50 , 51 ]. In another study, the pharmacokinetics of KJA were studied, and the anti-angiogenic role was investigated in EA.hy926 cell lines.…”
Section: Introductionmentioning
confidence: 99%